Pentingnya Kebijakan Pendidikan Hukum untuk Mencegah Bullying di Lingkungan di Madrasah Ibtidaiyah Mathlaul Huda Cicalengka - Muhamad Miftahul Munjiat; Fitriyah Fitriyah; Jalaludin Jalaludin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Bullying, a persistent and intentional form of aggressive behavior, has become a major issue affecting students in educational institutions worldwide. Its negative impacts on victims’ emotional well-being, academic performance, and psychological health have raised serious concerns among educators and policymakers. This study aims to examine the importance of legal education policies in preventing bullying within the learning environment of Madrasah Ibtidaiyah Mathlaul Huda Cicalengka. The research employs a normative legal approach using secondary data, which includes primary legal materials, secondary sources, and tertiary references. The data were analyzed through descriptive analytical methods to provide a comprehensive understanding of how legal education can serve as a preventive mechanism against bullying. The findings reveal that legal education significantly contributes to shaping students’ awareness of their rights and obligations, fostering a culture of respect and responsibility. By integrating legal education into school programs, students are better equipped to recognize and respond to bullying behaviors, both as potential victims and as witnesses. Consequently, the implementation of legal education policies is proven to be an essential preventive strategy in creating a safer, more inclusive, and law-abiding school environment.